On the Theoretical Backgrounds of Dialogue-Polilogue Transformation: Social and Philosophic Aspect - Ivanova, Yevgenya; Ponomarev, Vladimir (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The article reveals the variations of human adaptability to another subject in a multicultural society. In the article the author’s definition of a polylogue as a modern type of dialogue is given. Polylogue is an agent of meaning–form interaction of subjects, emerging with an unpredictable outcome and expressing particular logic of an intersubjective event. The author gives a comparative description of polylogue and discourse that helps to identify areas of discourse in the polylogue structure and its value.